Membangun Komitmen Aktivitas Karyawan Kelurahan Tegal Sari Mandala III Medan di Era Digital melalui Desain Komunikasi Organisasi yang Efektif - Delima, Wirda; Syukur Kholil (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Abstract This research aims to investigate the role of technology and digital communication in building commitment to employee activities in Tegal Sari Mandala III Medan Village in the digital era through effective organizational communication design. Employee activity commitment is a key factor that influences organizational performance and success. However, the digital era brings new challenges in building employee commitment through changes in communication and interaction patterns in the work environment. Using a mixed quantitative and qualitative approach, this research combines surveys, in-depth interviews, and participant observation to collect data. The research results show that the effective use of digital communication technology, such as email, instant messaging applications, and online collaboration platforms, has a significant positive relationship with the level of employee activity commitment. The more effective the use of digital communication technology, the higher the level of affective, sustainable and normative commitment that employees have. This research also identified challenges in implementing digital communication technology and effective communication design, such as varying levels of digital literacy among employees. To overcome these challenges, organizations need to provide training and mentoring to employees, as well as adopt an integrated communication approach. In general, this research confirms that efficient organizational communication design, supported by the appropriate use of digital communication technology, can be a key factor in strengthening employee engagement in the digital era. Organizations that are able to optimize the potential of technology and digital communications well will have a competitive advantage in building a team of human resources that is qualified and has a high level of commitment.